Eutrophication shifts microbial communities and life-history strategies in the Yangtze River Estuary - Li, Haizhou; Zhao, Feng; Yang, Qunhui; Chen, Lang; Zhou, Jin (Frontiers in Microbiology, 2025)
Marginal seas are increasingly impacted by anthropogenic activities, leading to widespread eutrophication, yet the responses of marine microbial communities remain poorly understood. We compared sediments from the highly eutrophic Yangtze River Estuary (YRE) and the oligotrophic East China Sea (ECS) to examine how eutrophication alters microbial abundance, community structure, assembly processes, functional profiles, and life-history strategies. Our results showed that YRE sediments harbored significantly higher microbial abundance (1.3 × 108-1.1 × 109 cells g−1 vs. 8.0 × 107-7.1 × 108 cells g−1), Chao1 richness (9,782–18,129 vs. 9,366–14,903), and Shannon diversity (6.19–7.47 vs. 6.05–7.07). Functional profiling revealed an enrichment of nitrogen- and carbon-cycling genes, human pathogens, and antibiotic-resistance genes in YRE. Life-history traits in YRE microbial communities showed higher average 16S rRNA gene copy numbers (median 2.75 vs. 2.56), greater codon usage bias (0.0181 vs. 0.0178), higher maximum predicted growth rates (0.1054 vs. 0.0951 h−1), larger genome sizes (5.59 vs. 5.46 Mb), higher GC content (56.43 vs. 55.83%) and increased transposase abundance (3.46 vs. 1.71%), collectively indicating a shift from K-strategists to r-strategists in the eutrophic environment. Neutral and null model analyses, and statistical analyses revealed that human activities, especially those altering water quality and chemistry, drive significant shifts in microbial community structure, function, and assembly processes, which in turn reshape microbial life-history strategies in estuarine benthic ecosystems.